Evaluation of the knowledge, attitude and awareness in prevention of dental caries amongst paediatricians - P, Poornima; Bajaj, Meghna; NB, Nagaveni; KB, Roopa; IE, Neena; KP, Bharath (International Journal Of Community Medicine And Public Health, 2017)
Background:Early assessment of the oral health status of children has the potential to reduce or even eliminate oral diseases. Paediatricians are considered a perfect and reliable source for oral health control and prevention. In dentistry, clinical practice is directed towards attitudes that promote oral health and the paediatricians occupy a privileged position in this process. The purpose of this study was to evaluate the knowledge, attitude and awareness of paediatricians in the prevention of dental caries in 3 district quarters, India. Methods:A cross-sectional survey was undertaken among 123 registered paediatricians in Indian Academy of Paediatrics (IAP) Karnataka directory and digest 2011-2013, Karnataka society. Out of which, 42 did not participate as their email address were not available. 29 sets of questions were mailed to all 81 paediatricians. Results:The response rate of the survey was 90% (70 out of 81), a total of 59% felt that the frequency of Early Childhood Caries (ECC) in their O.P.D was at least once a week. 51% responded that bacteria causing dental caries cannot be transmitted between mother and child. 53% felt that 1 year would be ideal for first dental visit. 64% of pediatricians were not aware that fluoride dentifrices and dental sealants will prevent dental caries. Conclusions:In general, pediatricians’ knowledge, attitudes and awareness regarding oral health and prevention of dental caries was not satisfactory. It is essential to develop oral health information programs to pediatricians.